Macroeconomic Factors on Stock Return at IDX Value 30 - Candy Candy; Jacelyin Jacelyin (Jurnal Indonesia Sosial Teknologi, 2024)
This study examined factors including oil prices, foreign exchange rates, consumer price index, gross domestic product, and foreign direct investment on stock return. This study used secondary data as a basis for research by obtaining information for 30 companies registered at IDX Value 30. This research uses panel regression to show the effect of each independent variable on stock return. According to the result, IDX Value 30 stock return is significantly positively impacted by gross domestic product, consumer price index, and foreign direct investment. Meanwhile, foreign exchange rates and oil prices negatively affect the stock return.